Multiattempt Quizzes in an MBA‐Level Statistics Course. (10th December 2020) - Robbins, Thomas R.
ABSTRACT: Statistics is a difficult subject for many students, but it is also a requirement for most graduate‐level business programs. Mastery of difficult subject matter is achieved through repetition. In this article, we review the process for setting up a multiattempt quiz system in an MBA‐level introductory statistics course and investigate the impact it had on student behavior and learning. We analyzed a dataset of more than 3, 000 quiz attempts to determine the impact repeated trials had on the time required to complete the quiz and the resulting score. We also examined the probability students will make an additional attempt and students' bias for a round number score. We found that scores improved and that quiz duration times decreased with repetition. We also discovered that student's preference to achieve round number goals impacts their willingness to make additional attempts.